Continuum Model of Orthotropic Tensegrity Plate-Like Structures with Self-Stress Included - AL SABOUNI-ZAWADZKA, Anna; KŁOSOWSKA, Joanna; OBARA, Paulina; GILEWSKI, Wojciech (Engineering Transactions, 2016)
A continuum model of the orthotropic tensegrity plate-like structures with self-stress included is proposed within the six-parameter flat shell theory. This approach allows to simplify calculations, that is, it is not necessary to describe the whole complex tensegrity cable-strut structure with the use of computational methods. Average displacements, strains and internal forces for orthotropic tensegrity plate-like structures can be determined within the model. The closed form solutions for selected tensegrity plate strips and simply supported rectangular plate with sinusoidal load are presented in the paper. Tensegrity modules, which are based on the four-strut expanded octahedron modules with additional connecting cables are proposed as the examples. Self-stress and some geometrical parameters are introduced for parametric analysis.